Knowledge, attitude, and practice towards COVID-19 prevention: a survey of Sudanese people - Alzain, Mohamed Ali; Elsser, Najm Eldinn; Asweto, Collins Otieno; Alsese, Mohammed Mohamoud; Humaida, Mohammed Ismail; Kassar, Ahmed; Abdelaziz, Mohamed Osman (International Journal Of Community Medicine And Public Health, 2021)
Background: The awareness and belief of people on coronavirus disease 2019 (COVID-19) prevention often influence their practices toward the disease. Therefore, it is essential to assess people’s knowledge, attitude, and practice towards COVID-19 prevention; to inform policymakers. Methods: An online survey was conducted on 1455 Sudanese adults using a pretested questionnaire. Chi-square test, spearman’s correlation, and logistic regression were used to analyse the data using statistical package for social sciences (SPSS) version-25. Results: The study found relatively good knowledge, attitude, and practice on COVID-19 prevention with overall correct rates of 84.6%, 88.8 %, and 78.6%, respectively. Furthermore, knowledge was positively correlated with attitude (r=0.355, P<0.001). Participants with good knowledge were more likely to have a positive attitude and practice (OR=1.36; 95%CI:1.08-1.71; OR=1.52; 95%CI:1.36-1.71), respectively than those with insufficient knowledge. While participants with a positive attitude were more than two times (OR=2.36; 95%CI:1.86-2.99) more likely to have good practice than a negative attitude. Moreover, females and married were more likely to have good practice (OR=1.37; 95%CI:1.10-1.69; OR=1.26; 95%CI:1.02-1.55), and positive attitudes (OR=1.39; 95%CI: 1.10-1.77; OR=1.45; 95% CI:1.15-1.84), respectively than their corresponding targeted counterparts. Furthermore, certain occupations (housewife, no worker, and employed) were more likely to have positive attitude and practice than the student (p<0.05). Besides, considerable participants had misconceptions regarding; effectiveness of antibiotics in combating COVID-19 (32%); almost two-thirds of participants either never wearing masks or sometimes. Conclusions: The finding concluded that relatively good knowledge, positive attitude, and desired practices against prevention of COVID-19. Therefore, a great emphasis on health awareness campaigns should focus on risk-taking practice and remove misconceptions.